Measurement method of the IGBT chip temperature fluctuation based on electrothermal model derivation. (December 2022) - Li, Lie; He, Yigang; Du, Bolun
Abstract: The IGBT chip temperature is an important index affecting device reliability. Due to the existence of packaging, the temperature data of the IGBT chip is difficult to obtain directly. Because the large IGBT switching frequency, the temperature changes quickly. The chip junction temperature fluctuation is too difficult to measure. Based on the Cauer electrothermal coupling model, this paper deduces the calculation formula of the IGBT chip temperature fluctuation. Through the on-stage voltage, collector current, thermal resistance, thermal capacitance, on time and off time that can be directly monitored, the chip temperature fluctuation inside the package can be calculated. Then the accuracy of the calculation formula of temperature fluctuation is verified by experimental method, and the experimental results confirm the feasibility of this method. The chip temperature fluctuation monitored by this method is the premise for the lifetime prediction and reliability research of the IGBT, which plays a great role in the engineering field.